Online monitoring method of mine-used high voltage cable insulatio - ZHANG Xiao; WANG Yanwen; ZHAO Yongmei; HOU Linan; BAI Shuju (Gong-kuang zidonghua, 2017)
In order to monitor insulation condition of mine-used high voltage cable in real time, an online monitoring method of mine-used high voltage cable insulation based on wide area measurement system(WAMS) was proposed. In the method, real-time voltage and current of cable ends are obtained synchronously by use of WAMS, and insulation resistance and equivalent capacitance of cable are derived through establishment of equivalent circuit model of cable to ground, so as to realize dynamic monitoring of cable insulation condition. The simulation results show that measurement error of the method decreases with increase of cable insulation deterioration, which meets precision requirement of online monitoring of mine-used high voltage cable insulation.